Evaluation of GSMaP Satellite Precipitation over Central Vietnam in 2000-2010 Period and Correction Ability - Thanh Hang, Vu; Thi Thanh Nga, Pham; Thanh Hà, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2018)
Abstract: Daily/Monthly precipitation of GSMaP is compared with observation at 10 stations over Central Vietnam in the 2000-2010 period. Evaluation indices used in this study include the correlation coefficient (r), relative bias (B), probability of detection (POD) and false alarm ratio (FAR). The results show the agreement betwween the first rainy month over 100mm and the maximum rainy month between GSMaP and observation, however, the duration of rainy months over 100mm of GSMaP is shorter than that of observation. GSMaP precipitation often underestimates compared to observation in October-December at most stations. It can be seen that monthly correlation coefficients are often positive at most stations when evaluating daily precipitation, the lower values are often found in January and February. Positive relative biases are observed in April-September at most of North Central stations, while those often occur in July-September at South Central stations. Negative relative biases can be found in October until March of the next year at most stations. The good POD and FAR values are given at 0-6mm/day threshold and the worse values are found at 6-16mm/day threshold. After applying correction methods, the GSMaP precipitation is much better agreement with observation, especially in underestimated rainy months. Keywords: Precipitation, GSMaP, evaluation, correction. References: [1] Hong Y., Adler R. F., Negri A., Huffman G. J., 2007, Flood and landslide applications of near real-time satellite rainfall products, Natural Hazards, 43(2), 285-294. [2] Kidd C., Levizzani V., Turk J., Ferraro R., 2009, Satellite precipitation measurements for water resource monitoring, Journal of the American Water Resources Association, 45(3), 567-579. [3] Shrestha M.S., Takara K., Kubota T., Bajracharya S.R., 2011, Verification of GSMap rainfall estimates over the central Himalayas, Hydraulic Engineering, 67(4), I37-I42. [4] Fukami K., Shirashi Y., Inomata H., Ozawa G., 2010, Development of integrated flood analysis system (IFAS) using satellite-based rainfall products with a self-correction method, International centre for water hazard and risk management under auspices of UNESCO (ICHARM), Public Works Research Institute, Tsukuba, Japan. [5] Kubota T., Ushio T., Shige S., Kida S., Kachi M.,Okamoto K., 2009, Verification of high resolution satellite-based rainfall estimates around Japan using a gauge calibrated ground radar data set, Journal of the Meteorological Society of Japan, 87A, 203-222. [6] Makino S., 2012, Verification of the accuracy of rainfall data by global satellite mapping of precipitation (GSMaP) Product, Yamaguchi University Thesis. [7] Seto S., 2009, An evaluation of overland rain rate estimates by the GSMaP and GPROF Algorithm: the role of lower frequency channels, Journal of the Meteorological Society of Japan, 87A, 183-202. [8] Tian Y., Peters-Lidard C.D., Adler R.F., Kubota T., Ushio T., 2009, Evaluation of GSMaP precipitation estimates over the contiguous United States, Journal Hydrometeorology, 11, 566-574. [9] Fu Q., Ruan R., Liu Y., 2011, Accuracy assessment of Global Satellite Mapping of Precipitation (GSMaP) product over Poyang lake basin, China, Procedia Environmental Sciences, 10, 2265-2271. [10] Chen Z., Qin Y., Shen Y., Zhang S., 2015, Evaluation of Global Satellite Mapping of Precipitation project daily precipitation estimates over the Chinese Mainland, Advances in Meteorology, 1-15. [11] Thanh N.D, Jun M., Hideyuki K., Hoang Hai B., 2013, Monthly adjustment of Global Satellite Mapping of Precipitation (GSMaP) data over the VuGia-ThuBon River basin in Central Vietnam using an artificial neural network, Hydrological Research Letters, 7(4), 85-90. [12] Ushio T., Sasashige K., Kubota T., Shige S., Okamoto K., Aonashi K., et al., 2009, A Kalman filter approach to the global satellite mapping of precipitation (GSMaP) from combined passive microwave and infrared radiometric data, Journal of Meteorological Society of Japan, 87A, 137-151. [13] Okamoto K., Iguchi T., Takahashi N., Ushio T., Awaka J., Kozu T., et al., 2007, High precision and high resolution global precipitation map from satellite data, ISAP 2007, Nigata, Japan. [14] Damrath U., 2002, Verification of the operational NWP models at DWD, Offenbach, Germany.